Central bank reserves and sovereign wealth management - Berkelaar, Arjan B.; Coche, Joachim; Nyholm, Ken. (Basingstoke [England] ; New York : Palgrave Macmillan, 2010)
"This book comprises the papers presented and discussed at the SAA conference, held 24-25 November 2008. It offers an exchange of views on technical and implemental issues of financial models relevant for strategic asset allocation"--Provided by publisher.
Includes bibliographical references and index.
oif 11/06/15
Loan
Keywords: Banks and banking, Central; Bank reserves